Synthesis and characterizations of bis(phenoxy)-amine tin(II) complexes for ring-opening polymerization of lactide - Siriwan Praban (2020)
© 2019 Wiley Periodicals, Inc. A series of tin(II) complexes supported by N2O2 bis(phenol)-amine ligands were prepared from the reactions of the corresponding ligands with Sn[N(SiMe3)2]2 in benzene at room temperature. The ligands were designed to have different substituted group at the ortho-position on the aryl rings (R = tBu, CH3) and N-containing side arm (E = CH2NEt2 and pyridine) giving a variation of tin(II) complexes (R = tBu, E = CH2NEt2, 2a; R = tBu, E = py, 2b; R = CH3, E = CH2NEt2, 2c; R = CH3, E = py, 2d). All complexes were characterized by NMR spectroscopy and single-crystal X-ray analysis. The single-crystal X-ray crystallography revealed that all complexes have a monomeric four-coordinate tin center with a distorted seesaw structure. All complexes are active for solvent-free polymerization of l-lactide at 120 °C giving poly(l-lactide) with narrow to moderate dispersity (Ð = 1.12–1.56). In the presence of benzyl alcohol during the polymerization, the resulting polymer was found to be linear having benzyl alcohol as the end group while, in the absence of benzyl alcohol, the polymer was cyclic. The large tBu group at the ortho-position was found to decrease polymerization activity while the more basic CH2NEt2 group was found to increase the polymerization activity. The polymerization of rac-lactide under a similar condition gave PLA having a slight heterotactic bias for all catalysts. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2104–2112.